Pulse monthly steroids during an elective interruption of natalizumab: a post-marketing study - Borriello, G.; Prosperini, L.; Mancinelli, C.; Giannì, C.; Fubelli, F.; Pozzilli, C. (European journal of neurology, 2012)
Background and purpose:  Temporary discontinuation of natalizumab is sometimes considered as the observed risk of progressive multifocal leukoencephalopathy (PML) in patients with multiple sclerosis (MS). However, interruption of natalizumab may result in a re‐start of disease activity. Methods:  In this prospective post‐marketing study, 23 patients with MS treated with natalizumab elected a trial of treatment interruption (90–150 days) because of safety concerns on the risk of developing PML. To reduce the risk of disease activity return, patients received monthly intravenous (i.v.) steroid pulses before natalizumab re‐start. Results:  Despite the steroid coverage, seven patients (30.4%) had an active scan during the natalizumab interruption period; of these, four also had a concomitant clinical exacerbation. Conclusions:  Our findings suggest that i.v. steroids are not currently recommendable as drug coverage during a scheduled treatment interruption period. Click here to view the accompanying paper in this issue.